Selected problems of administrative detention based on the art. 40 Act on Upbringing in Sobriety and Counteracting Alcoholism (Discourse of Law and Administration, 2021)
The article was devoted to the analysis of the so-called administrative detention, referred to in Article 40 paragraph 1 of the Act on Upbringing in Sobriety and Counteracting Alcoholism. The author searches for answers to questions about the limits of legitimacy of police actions when administratively detaining a citizen. She also analyses whether a person under the influence of alcohol can be arrested and taken to a so be ring station in every case, and discusses the consequences of an illegal arrest both from the point of view of the arrested person and the responsibility of the arresting officer.
Keywords: administrative detention; sobriety and alcoholism prevention act; unlawful detention; liability for unlawful detention